The Effectiveness of Two Stay Two Stray (TSTS) Cooperative Learning Model in Improving Students 'Critical Thinking Skills - Diaz Apriakanti; Mobinta Kusuma; Muriani Nurhayati (Journal of Science Education Research, 2020)
The purpose of this study was to determine (1) the differences in students' critical thinking skills in natural science subjects between those who use the Two Stay Two Stray cooperative learning model (TSTS) and those who use the Problem Based Learning (PBL) learning model (2) the effectiveness of Two Stay Two Stray (TSTS) type of cooperative learning models and Problem Based Learning (PBL) learning models in improving students' critical thinking skills. This type of research was an experiment with a Posttest-Only Control Design group method. The sampling technique used was Cluster Random Sampling to determine the experimental class and the controlled class. Data collection techniques were the test. Furthermore, the research instrument used the final test to measure students' critical thinking skills. From the results of data analysis, it was obtained the results of hypothesis testing and hypothesis testing on the effectiveness of students' critical thinking skills. The calculation results of the hypothesis test for differences in critical thinking skills of students using the Independent Samples t-test showed tcount greater than ttable (14.710 greater than 1.674) and a significance value of 0.000 less than0.05, while the results of the effectiveness test on students' critical thinking skills used the One Sample t-test. The test shows the value of tcount greater than ttable (11.654 greater than 1.708) and a significance value of 0.000 less than0.05. Thus, it can be concluded that the Two Stay Two Stray (TSTS) cooperative learning model can improve students' critical thinking skills.